Effectiveness of Massage Gun and Foam Roller Methods on Fatigue Recovery in Football Athletes - Reza Pahlevi; Rusdiana , Agus; Haryono, Tono; Ikhwan Hidayat, Iwa; Kurniawan, Tian (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
An athlete's performance in a match can be influenced by various factors, including physical condition and fatigue. Studies indicate that fatigue leads to decreased physical and technical performance in soccer players. This study aimed to compare the efficacy of using a massage gun versus a foam roller for fatigue recovery in football athletes. Employing an experimental pretest-posttest design, the study assessed the impact of massage guns (MG) and foam rollers (FR) on 8 football athletes. The research utilized a lactic acid level test with Accutrend Lactate. Results revealed a t value of 0.982 with a significance level (2-tailed) of 0.364, indicating no significant difference between the two recovery methods in reducing fatigue levels among football athletes. Furthermore, the paired sample test showed a significance level (2-tailed) of 0.004 for the foam roller group and 0.006 for the massage gun group, both below 0.05. Consequently, the study concludes that foam rollers are more effective than massage guns in alleviating fatigue in football athletes.